2013
DOI: 10.2172/1110480
|View full text |Cite
|
Sign up to set email alerts
|

Technetium Removal Using Tc-Goethite Coprecipitation

Abstract: Executive SummaryThis report describes the results from laboratory tests performed at Pacific Northwest National Laboratory for the U.S. Department of Energy (DOE) EM-31 Support Program (EMSP) subtask, "Low temperature waste forms coupled with technetium removal using an alternative immobilization process such as Fe(II) treated-goethite precipitation" to increase our understanding of 99 Tc long-term stability in goethite mineral form and the process that controls the 99 Tc(VII) reduction and removal by the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Hence, it is suggested that alteration of the glasses under thoroughly reducing conditions sustained over very long time will keep the Tc ions confined to an insoluble secondary phase akin to pyrolusite, thus preventing their hazardous accumulation in the biosphere. Recent research suggests that Tc(IV) ions can be sorbed onto FeS 2 surfaces or incorporated in iron oxides such as hematite (α‐Fe 2 O 3 ) or magnetite (Fe 3 O 4 ) as well as iron oxihydroxides such as goethite (α‐FeOOH) . The mechanism relies on direct substitution of Tc(IV) onto Fe(III) lattice sites that may be retained stably under environmental conditions to be expected in a nuclear waste disposal vault.…”
Section: Extension To Nuclear Waste Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is suggested that alteration of the glasses under thoroughly reducing conditions sustained over very long time will keep the Tc ions confined to an insoluble secondary phase akin to pyrolusite, thus preventing their hazardous accumulation in the biosphere. Recent research suggests that Tc(IV) ions can be sorbed onto FeS 2 surfaces or incorporated in iron oxides such as hematite (α‐Fe 2 O 3 ) or magnetite (Fe 3 O 4 ) as well as iron oxihydroxides such as goethite (α‐FeOOH) . The mechanism relies on direct substitution of Tc(IV) onto Fe(III) lattice sites that may be retained stably under environmental conditions to be expected in a nuclear waste disposal vault.…”
Section: Extension To Nuclear Waste Glassesmentioning
confidence: 99%
“…Recent research suggests that Tc(IV) ions can be sorbed onto FeS 2 surfaces 102 or incorporated in iron oxides such as hematite (a-Fe 2 O 3 ) 103 or magnetite (Fe 3 O 4 ) 104 as well as iron oxihydroxides such as goethite (a-FeOOH). 105,106 The mechanism relies on direct substitution of Tc(IV) onto Fe(III) lattice sites that may be retained stably under environmental conditions to be expected in a nuclear waste disposal vault.…”
Section: Waste Glassesmentioning
confidence: 99%
“…If such Tc incorporation into these solid phases takes place, then the mobility of Tc may depend on the stability of the host phase and not necessarily upon the reoxidation kinetics. a The coordination number refers to the number of associated ligands and LS and HS stand for "low-spin" and "high spin" configurations Um et al (2010Um et al ( , 2011aUm et al ( , 2012Um et al ( , and 2013Westsik et al 2011) have been conducting experimental studies on sequestering Tc in goethite and other iron oxide solid phases. Their first studies showed that goethite could sequester significant amounts (>90% of the initial Tc mass) of Tc present in simple and caustic brine simulants as long as additional aqueous Fe(II) was added and the pH of the slurry was adjusted to neutral to mildly caustic conditions.…”
Section: Iron-technetium Oxidesmentioning
confidence: 99%
“…This post-Tc-reduction/incorporation step forms a physical armoring layer that provides a second barrier to leaching and reoxidation of Tc(IV) (Um et al 2011a). Um et al (2013) showed that Fe(OH) 2 (s) readily reduced and then sequestered Tc and transformed to a mixture of magnetite, maghemite, 1 and goethite even at room temperature and circumneutral pH conditions. Removal of 99 Tc from solution by Fe(OH) 2 (s) was fast, and more than 95% of the initial 99 Tc (10 -5 M) was removed from Tc(VII)-spiked distilled water even without aqueous Fe(II) addition.…”
Section: Iron-technetium Oxidesmentioning
confidence: 99%
See 1 more Smart Citation